463 BONE MARROW TREATED WITH WNT3A AND WNT5A RESULTS IN A CHANGE IN THE CELLULAR DISTRIBUTION OF DIFFERENTIATED AND UNDIFFERENTIATED INFLAMMATORY CELL TYPES. (10th December 2015) - Fathke, C.; Wilson, L.; Hocking, A.; Isik, F. F.
Abstract : Background: During adult cutaneous wound healing the acute inflammatory stage is essential for proper wound repair. Various conditions dysregulate the inflammatory phase and a chronic inflammatory cycle ensues. Chronic inflammation is characterized by the persistent presence of monocytes, lymphocytes and plasma cells in the injured region. It prevents epithelialization and results in the necrosis of the surrounding tissue. Chronic inflammation is thought to be the etiology for most non-healing wounds. It also remains one of the most elusive problems to characterize at the cellular and molecular level. It is not clear why the inflammatory process becomes dysregulated or exactly what molecular signals have gone awry. One of the candidates for the molecular signals involved in inflammation is the Wnt family of signaling molecules. These glycoproteins regulate proliferation and differentiation of cells by signaling through the Wnt/β-catenin or Wnt/Ca2+ pathways Recent work in our lab suggests that Wnt signal transduction may play a role in wound healing and in the regulation of inflammation during the cutaneous healing process. Our hypothesis is that the Wnt pathway is an adjuvant for inflammatory cell differentiation. Study Design and Methods: An in vitro model was used where whole bone marrow was extracted from the femur and tibia of TOPGAL mice and cultured for 24, 48 or 72 hours in conditioned media containing either control, Wnt3a, a mediator of the Wnt/}158}-catenin or Wnt5a which signals through the Wnt/Ca2+ pathway. At the various endpoints the cells were analyzed by FACS for various markers including Gr1, a granulocyte marker; F4/80, a marker of monocytes and macrophages; CD31, and endothelial cell, leukocyte marker; Sca1, a marker of bone marrow stem cells; CD117 a marker of hematopoetic stem cells.. Results: Bone marrow cells treated with Wnt3a conditioned media showed decreased numbers of Sca1+ cells at 24 hours (p=0.06) and lower levels of F4/80+ cells at 48 hours (p=0.03) when compared to control. When the bone marrow cells were treated with Wnt5a conditioned media at 24 hours there was a decrease in Sca1+ cells (p=0.06) and an increase in CD117+ cells (p=0.08). At 48 hours there was a decrease in F4/80 (p=0.04), CD31 (p=0.04), Sca1 (p=0.007) and CD117 (p=0.03) cells when compared to control. Conclusion: Both Wnt3a and Wnt5a have an effect on the cellular distribution of differentiated and undifferentiated cells in cultured bone marrow.